2011
DOI: 10.1103/physrevb.83.132509
|View full text |Cite
|
Sign up to set email alerts
|

Structure of vacancy-ordered single-crystalline superconducting potassium iron selenide

Abstract: With single crystal X-ray diffraction studies, we compare the structures of three sample showing optimal superconductivity, K0.774(4)Fe1.613(2)Se2, K0.738(6)Fe1.631(3)Se2 and Cs0.748(2)Fe1.626(1)Se2. All have an almost identical ordered vacancy structure with a (√5 x √5 x 1) super cell. The tetragonal unit cell, space group I4/m, possesses lattice parameters at 250K of a = b = 8.729(2) Å and c = 14.120(3) Å, a = b = 8.7186(12) Å and c = 14.0853(19) Å and at 295 K, a = b = 8.8617(16) Å and c = 15.304(3) Å for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
128
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(137 citation statements)
references
References 33 publications
7
128
2
Order By: Relevance
“…The Fe-Se distances determined by EXAFS data in different polarizations on two edges are similar within experimental uncertainties (upper panel). However, both Fe-Se and Fe-Fe distances (lower panel) appear slightly shorter than the average bondlengths determined by diffraction studies [17,18,19,20,33]. This may be due to largely disordered structure, as seen in the glasses [34,35].…”
Section: Resultsmentioning
confidence: 83%
“…The Fe-Se distances determined by EXAFS data in different polarizations on two edges are similar within experimental uncertainties (upper panel). However, both Fe-Se and Fe-Fe distances (lower panel) appear slightly shorter than the average bondlengths determined by diffraction studies [17,18,19,20,33]. This may be due to largely disordered structure, as seen in the glasses [34,35].…”
Section: Resultsmentioning
confidence: 83%
“…At the temperatures of interest here, K 0.80 Fe 1.76 Se 2.00 adopts a vacancy-ordered I4/m modification of the parent ThCr 2 Si 2 −type I4/mmm structure with iron essentially filling a 16i site and leaving ordered vacancies on the (almost) empty 4d site 26,31 . Occupations of ∼8% for the Fe-4d site have been reported 31 .…”
Section: Resultsmentioning
confidence: 98%
“…Occupations of ∼8% for the Fe-4d site have been reported 31 . If we assume full occupation of the Fe-16i site in our sample, this leaves 9% of the iron in the 4d site.…”
Section: Resultsmentioning
confidence: 99%
“…One superconducting sample from a systematic synthesis study of another group [21] is found to be K 0.737(6) Fe 1.631(3) Se 2 in the singlecrystal x-ray diffraction study [20], while another superconducting sample to be K 0.83(2) Fe 1.64(1) Se 2 in a powder neutron diffraction refinement study [10]. Thus, the iron valance in the superconducting samples is very close to but not exactly at 2+, similar to that in the previously discovered iron chalcogenide superconductors Fe 1+δ (Se,Te) [8,9], but very different from the conclusion of the ARPES studies which claim intact FeSe layers in A 0.8 Fe 2 Se 2 [17,22,23].…”
Section: Sample Composition and Crystal Structure Of The Superconductorsmentioning
confidence: 99%
“…1. The ordered structure is refined in the tetragonal I4/m unit cell, and the structure parameters are tabulated in [10,20]. The prominent structural feature of the superconducting sam- ples is the almost empty 4d Fe1 site with an occupancy n(4d) at a few percent and the full occupancy of the 16i Fe2 site, see TABLE II, below room temperature.…”
Section: Sample Composition and Crystal Structure Of The Superconductorsmentioning
confidence: 99%